"It's not something we thought about": teachers' perception of historiography and narratives. Issue 1 (21st May 2018) - Brown, Sarah Drake; Hughes, Richard L.
Abstract : Purpose: The purpose of this paper is to examine three high school teachers' beliefs about how their understanding of historiography influences their teaching. Design/methodology/approach: The authors engaged in a qualitative multiple-case study based on semi-structured interviews and artifact analysis. Findings: The analysis describes the teachers' understanding of historiography in relation to ideas about historical perspective-taking, textbook use, the incorporation of primary sources in the classroom, and tensions between teaching content and teaching skills. The study concludes that while undergraduate exposure to historiography is potentially useful and can help history teachers manage the complexity of the profession, drawing upon historiographical understandings in order to recognize the construction of historical narratives in the classroom remains a persistent challenge. Originality/value: Much of the work addressing the potential role of historiographical understanding for teachers has focused on teacher preparation and the ideas held by teaching candidates. This research emphasizes experienced teachers' beliefs about the role that historiography plays in their teaching.